2004
DOI: 10.1210/jc.2003-031327
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Controls Lipolysis by Up-Regulating α2A-Adrenergic Receptors Directly in Human Adipose Tissue through the Estrogen Receptor α. Implications for the Female Fat Distribution

Abstract: Estrogen seems to promote and maintain the typical female type of fat distribution that is characterized by accumulation of adipose tissue, especially in the sc fat depot, with only modest accumulation of adipose tissue intraabdominally. However, it is completely unknown how estrogen controls the fat accumulation. We studied the effects of estradiol in vivo and in vitro on human adipose tissue metabolism and found that estradiol directly increases the number of antilipolytic alpha2A-adrenergic receptors in sc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
199
1
4

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(209 citation statements)
references
References 43 publications
5
199
1
4
Order By: Relevance
“…30,31 Estrogen may also decrease lipolysis in adipose tissues by increasing the number of antilipolytic a2A-adrenergic receptors. 20,32 Besides, it was suggested that estrogen may attenuate growth hormone (GH) signaling 33 and GH was reported to increase lipid oxidation 34 and reduce body fatness. 35 In sum, estrogen can affect obesity phenotypes through different pathways which may interact with each other, and much work is needed to understand its precise role in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Estrogen may also decrease lipolysis in adipose tissues by increasing the number of antilipolytic a2A-adrenergic receptors. 20,32 Besides, it was suggested that estrogen may attenuate growth hormone (GH) signaling 33 and GH was reported to increase lipid oxidation 34 and reduce body fatness. 35 In sum, estrogen can affect obesity phenotypes through different pathways which may interact with each other, and much work is needed to understand its precise role in obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Real-time quantitation of target gene to -actin mRNA was performed with a SYBR-Green real-time PCR assay using an ICycler from BioRad (Hercules, CA, USA) as described previously. 12 The target gene and -actin mRNA were amplified in separate tubes. The increase in fluorescence was measured in real time during the extension step.…”
Section: Lipolysismentioning
confidence: 99%
“…Trying to explain how estrogen promotes and maintains the typical female type of fat distribution, Pedersen et al [20] studied the effects of estradiol in vivo and in vitro on human adipose tissue metabolism and observed that estradiol administration attenuates lipolytic response in subcutaneous abdominal adipocytes, but not in intra-abdominal adipocytes. They found that estradiol directly increases the number of antilipolytic α-2A-adrenergic receptors in subcutaneous adipocytes and, in contrast, no effect of estrogen on α-2A-adrenergic receptor messenger RNA expression was observed in adipocytes from the visceral fat depots.…”
Section: Sex Hormones and Abdominal Obesitymentioning
confidence: 99%